The pilot : [videorecording (DVD)] - Davletyarov, Renat; Timoshkin, Alexey; Ashkenazi, Sergeĭ, 1949-; Fedorov, Petr, 1982-; Peskova, A. A.; Emelyanov, Maksim; Ihnow, Michael (Well Go USA Entertainment, 2022)
In December 1941, a German tank column is moving towards Moscow. During a mission to stop the enemy advance, Soviet pilot Nikolai Komlev's Il-2 is shot down in enemy territory. To survive, Komlev must face hunger, extreme cold, evading wild wolves, and avoiding Nazi soldiers. When he finally makes it back to safety, he faces the strongest challenge of them all.